Chromium free high temperature water-gas shift catalyst for the production of hydrogen from waste derived synthesis gas - Jha, Ajay; Jeong, Dae-Woon; Lee, Yeol-Lim; Jang, Won-Jun; Shim, Jae-Oh; Jeon, Kyung-Won; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Applied Catalysis A-General, 2016)
A comparative study between monometallic (Me-CeO2, Me =Zn, Cu, Fe and Co) and Ni-doped bimetallic (Me-Ni-CeO2) catalysts has been performed in the high temperature water-gas shift (HT-WGS) reaction using waste derived synthesis gas. Experimental results revealed that Me-Ni-CeO2 exhibited higher catalytic performance than simple Me-CeO2 catalysts. Within the Me-Ni-CeO2 series, Co-Ni-CeO2 exhibited excellent and stable catalytic performance (CO conversion > 90%) at a very high GHSV of 143,000 h(-1). The existence of high" concentration of Ce3+ ions and oxygen vacancies on the catalyst surface were responsible for the increased WGS activity of Co-Ni-CeO2. In addition, Co-Ni-CeO2 maintains a stable performance for 50 h. However, commercial Fe2O3-Cr2O3 catalyst showed a steep decline from their initial CO conversion values 15-10% within 5 h. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: CeO2; Co-Ni-CeO2; Lattice strain; oxygen vacancies; Water-gas shift

Effect of titration time on the catalytic performance of Cu/CeO2 catalysts for water-gas shift reaction - Na, Hyun-Suk; Shim, Jae-Oh; Jang, Won-Jun; Jeon, Kyung-Won; Kim, Hak-Min; Lee, Yeol-Lim; Lee, Da-We; Yoo, Seong-Yeun; Bae, Jong Wook; Rode, Chandrashekhar V.; Roh, Hyun-Seog (Catalysis Today, 2018)
We herein report the preparation of ceria (CeO2) via a simple precipitation method for use as a catalyst support in the water-gas shift (WGS) reaction. More specifically, we optimized the titration time required to obtain highly active CeO2-supported catalysts for the WGS reaction. As such, Cu was employed as the active metal coupled with the CeO2 support. Notably, the CeO2-0 supported Cu catalyst (where the precipitant was immediately injected into a cerium nitrate solution) exhibited the highest CO conversion at a gas hourly space velocity of 36,050 h(-1). This high catalytic activity of the Cu/CeO2-0 catalyst was mainly due to its high Brunauer-Emmett-Teller (BET) surface area, enhanced Cu dispersion, high number of oxygen vacancies, and enhanced reducibility.